RESPONS MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS VETERAN BANGUN NUSANTARA DALAM MENYELESAIKAN SOAL LOGIKA BERDASAR TAKSONOMI SOLO - Exacta, Annisa Prima; Sujadi, Imam; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract. The objectives of this research were: 1) to describe the response level of mathematics students in Veteran Bangun Nusantara University Sukoharjo based on SOLO taxonomy in solving logic problems; 2) to describe the characteristic of students response at each level of SOLO taxonomy; 3) to study if there is misconception at each level of SOLO taxonomy about students response.This research was a qualitative research. The subject in this research were the students of Mathematics Education, Veteran Bangun Nusantara University on the first semester academic year 2014/2015. The main instruments used in this research to collect the data was the researcher and the other instruments were test instrument and interview guide instrument. Data analysis technique was conducted by data reduction, data presentation and data verification or made conclusion. The conclusions as follows. 1) Students response level based on SOLO taxonomy in solving logic problems comprised prestructural, unistructural, multistructural, relational, and extended abstract, 2) Students response characteristic at each level of SOLO taxonomy as follows. a) Prestructural: the answer completely irrelevant, could not understand the problem given, could not connect the concept and the answer, and the answer was illogical. b) Unistructural: there was a clear and simple relationship between one concept to another but the core of concept widely was not yet understood. c) Multistructural: understood some of the components but still separated from each other so a comprehensive understanding was not formed, some simple connections have been established however metacognitive abilities have not appeared yet at this level. d) Relational: could connect the fact and the theory and also connect the action and the objective, showed understanding ability of some components from the whole concept, understood the role of the parts to the whole and has been able to apply a concept in similar circumstances, have better ability to expressed ideas and made some automatic repetition. e) Extended Abstract: have the ability to think conceptually, to connect not only limited to the concepts that have been given alone but with concepts beyond that, could made generalizations in different problems and made parables in specific situations. 3) Based on the 5 response level of SOLO that happened to students, scheme on each level as shown below. At prestructural and unistructural response levels that were students who have misconceptions. At the multistructural response level, there were students who have a scheme but invalid because the result of the first and second data collection was not the same. The first result were correct scheme but the second result were misconceptions. At the relational response level, there were students who have misconceptions and at the extended abstract response level, there were students who have a correct scheme or in other words did not experience misconceptions.Keywords: SOLO taxonomy, response level, scheme, misconception.